Konsep Bela Negara Dalam Perspektif Ketahanan Nasional - Soepandji, Kris Wijoyo; Farid, Muhammad (Jurnal Hukum & Pembangunan, 2018)
The 1945 Constitution of the Republic of Indonesia in an explicit manner stipulates that every Indonesian citizen has the obligation to participate in defending the state. This is stated on the article 27 clause 3 of the Constitution, which reads, “Each citizen shall have the right and duty to participate in the effort of defending the state”. In a more specific manner, state defending is also stated on article 9 clause 1 and 2 of the Law number 3 year 2002 on the State Defence. The article mentions that the effort on state defending is elaborated in the performance of state defence, which includes civic education, compulsory basic military training, voluntary or compulsory service in Indonesia Armed Forces, and professional service. However, at practical level, the effort on state defending has not yet been performed in a systematic manner, particularly with the absence of comprehensive state defending education system for young generation. This circumstance may affect to the national resilience, which is related to the dynamics of geopolitics. This article suggests a system of state defending education, starts from secondary (junior high school and senior high school) to the preparation for tertiary education levels or entrance into workforce. In the future, the system may become reference for the formulation of concept on curriculum, as well as policy and regulation on state defending